Comparative study on preferences and quality of poultry meat. - Triyantini .; Abubakar .; I.A.K Bintang; T Antawidjaja (Indonesian Center for Animal Research and Development (ICARD), 1997)
A study was conducted to examine physical and nutritional compositions as well as carcass preferences of broilers, native chickens, ducks and muscovy using 25 birds from each species . Parameters measured were : percentage of carcass, part of carcass and by-products, carcass quality, tenderness, water, protein, fat and ash contents of meat and skin . Preference test was conducted on thigh and breast meat, as well as whole carcass and cuts. The results of the study showed that the carcass quality of native chicken and ducks were better than the carcass of broilers and muscovy, and over 80% of them were considered as first class quality . The carcass percentage of broilers was higher than the native chickens, ducks and muscovy (P < 0 .01) . The tenderness of breast meat was not significantly different, (36 .16-40 .84 kg/second), however, the tenderness of broiler thigh meat was the highest (61 .77 kg/second) among other meat (P < 0 .01). Protein content of duck breast meat was the lowest, while the protein content of duck thigh meat and the muscovy were higher than that of broilers and native chickens (P < 0 .05) . Fat content of broilers thigh meat was the highest as compared to other poultry meats (P < 0 .01) . Organoleptic test showed that the taste of breast and thigh meat of native chicken, duck and muscovy were similar with that of broilers, however the appearance and color of carcass of broilers and muscovy were more accepted than that of native chickens and ducks (P < 0.05). The meat of native chickens, ducks and muscovy were considered as good protein sources as judged by the physical appearances, nutritional composition and the preferences test . Keywords : Poultry meat, quality, preference